Who can speak Lenape in Pennsylvania? Authentication and language learning in an endangered language community of practice. (March 2016) - Weinberg, Miranda; De Korne, Haley
Abstract: How are new speakers of an endangered language created? In this paper we draw on a three-year ethnographic case study to explore the processes through which a group of learners at a Pennsylvania college came to be identified as speakers of Lenape, a language indigenous to the eastern United States. Using a communities of practice framework, we analyze how language learning was facilitated and how the identities of community members were negotiated and contested through processes of authentication. A community of practice lens affords a useful framework for understanding how this successful learning community functioned, and for identifying factors that may benefit other language revitalization initiatives.